1964
DOI: 10.3181/00379727-116-29197
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Adenovirus Growth in African Green Monkey Kidney Cell Cultures by SV40

Abstract: Mixed infection with simian virus 40 (SV40) and adenovirus 1 2 can occur in African green monkey kidney (AGMK) cells in vitro, and electron micrographs demonstrating both viruses within the nucleus of a single cell have been presented ( 1 ) . Variable degrees of partial exclusion were produced by altering the time interval between inoculation of SV40 and adenovirus 12, and approximately 40% of the cells contained both viruses when the adenovirus was inoculated 24 hours after SV40(1). Further studies of AGMK c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
0
1

Year Published

1966
1966
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(88 citation statements)
references
References 0 publications
1
86
0
1
Order By: Relevance
“…A carboxy-terminal fragment of T-ag can relieve a block to Ad replication in monkey cells (Rabson et al, 1964 ;Kelley & Lewis, 1973 ;Cole et al, 1979) by an unknown mechanism. The hr\hf domain was identified because T-ag carboxy-terminal deletion mutants exhibited different growth properties in monkey cell lines ; these mutants grew well in BSC and Vero cells, but not in CV-1 cells (Lewis et al, 1983 ;Pipas, 1985 ;Tornow et al, 1985 ;Cole & Stacy, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…A carboxy-terminal fragment of T-ag can relieve a block to Ad replication in monkey cells (Rabson et al, 1964 ;Kelley & Lewis, 1973 ;Cole et al, 1979) by an unknown mechanism. The hr\hf domain was identified because T-ag carboxy-terminal deletion mutants exhibited different growth properties in monkey cell lines ; these mutants grew well in BSC and Vero cells, but not in CV-1 cells (Lewis et al, 1983 ;Pipas, 1985 ;Tornow et al, 1985 ;Cole & Stacy, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The block to replication of Ad2 in monkey cells can be overcome by coinfection with simian virus 40 (SV40; ref. 1) or by infection with Ad2-SV40 hybrid viruses (e.g., Ad2+ND1) that contain a segment of the SV40 genome encoding only the carboxyl terminus of the SV40 large tumor antigen (2)(3)(4)(5). In addition, mutants of human adenovirus have been isolated (Ad2hr400-403, Ad5hr404, Ad2+ND3hr600-603) that grow efficiently in monkey cells as well as human cells (6)(7)(8).…”
mentioning
confidence: 99%
“…The 5' ends of fiber messages from productively and abortively infected human and monkey cells were analyzed by a primer extension procedure. Single-stranded radiolabeled synthetic oligodeoxynucleotide primer complementary to the 5' end of the 1 main body of the fiber message was hybridized to RNA from productively or abortively infected cells and elongated with AMV reverse transcriptase to make complete cDNA copies of the 5' ends of fiber messages (Fig. 1).…”
mentioning
confidence: 99%
“…Rabson et al [25] found that the growth of adenovirus in African green monkey kidney cells was enhanced by mixed infection with SV40 which is quite distinct from adenovirus. Although the mechanism of this enhancement is unknown, it seems interesting to examine whether UV-irradiated adenovirus can be reactivated in the cell simultaneously infected with SV40.…”
Section: Comparison Of Survival Curves Of Uv-mentioning
confidence: 99%